Simultaneous bilateral optic neuritis in China: clinical, serological and prognostic characteristics. Issue 3 (11th January 2019) - Kang, Hao; Liu, Zihao; Li, Hongyang; Chen, Tingjun; Ai, Nanping; Xu, Quangang; Cao, Shanshan; Tao, Yong; Wei, Shihui
Abstract: Purpose: To analyse the clinical characteristics of simultaneous bilateral ON patients in China. Methods: This retrospective study was done on 51 primary bilateral ON patients between April 2008 and July 2016 at the Chinese People's Liberation Army General Hospital. Fifty eight primary unilateral ON patients formed the control group. Demographic data, clinical course, serum autoantibody status, connective tissue disorders, magnetic resonance imaging and visual functions were compared. Results: The mean age at disease onset in the bilateral group was younger than that of the unilateral group (p = 0.001). Cerebrospinal fluid (CSF) total cell count and CSF total protein were significantly higher in the bilateral group (p = 0.001, p = 0.025). Aquaporin‐4 (AQP4) antibodies were detected in 39% and 21% of the bilateral and unilateral patients, respectively (p = 0.03). Twenty two percent of the bilateral patients fulfilled the diagnosis of neuromyelitis optica (NMO); 7% in the unilateral group did so (p = 0.03). Serum autoantibodies (ANA, SSA, SSB, etc.) were found in 49% of the bilateral patients and 29% of the unilateral patients (p = 0.035). After treatment, the bilateral patients were significantly more prone to severe visual disability eventually than their unilateral counterparts (p = 0.002). Patients with MOG‐IgG (myelin oligodendrocyte glycoprotein‐IgG) represented 26% of the patients negative for AQP4‐IgG. Myelin oligodendrocyte glycoprotein‐IgG (MOG‐IgG) sero‐positive patients were more likely to recover than the other patients (p < 0.001). Conclusion: Simultaneous bilateral ON is a severe disorder closely related to serum AQP4‐IgG and MOG‐IgG, which are more likely to involve younger people and incur severe visual disability eventually. Myelin oligodendrocyte glycoprotein‐IgG (MOG‐IgG) sero‐positive patients have higher risk of ON relapses and better visual prognosis.